2019
DOI: 10.17113/ftb.57.02.19.6142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dehydrated Wheat/Rice Cereal Matrices on Probiotic Activity of Bifidobacterium animalis ssp. lactis BB-12®

Abstract: Three novel dehydrated wheat/rice cereal functional products with an addition of well documented probiotic Bifidobacterium animalis ssp. lactis BB-12® (BB-12®) were developed in Podravka factory for the infants older than 4 months: instant rice cereal, instant rice cereal with fruits and instant wheat cereal with vanilla. Notably, the number of viable BB-12® cells in each of the novel products was higher than the required minimal number of probiotic cells per gram of product (106 CFU/g) during the storage peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…BB-12 R CFU ranged from 1.8 × 10 7 to 3.2 × 10 8 log CFU/g (Graph A, Figure 2). This values are in line with the results that were obtained by Pavunc et al, who reported BB-12 R growth to be higher than 10 6 CFU/g in fermented cereal matrices [69].…”
Section: Viability Of Bb-12 R and Lgg R During Storagesupporting
confidence: 93%
“…BB-12 R CFU ranged from 1.8 × 10 7 to 3.2 × 10 8 log CFU/g (Graph A, Figure 2). This values are in line with the results that were obtained by Pavunc et al, who reported BB-12 R growth to be higher than 10 6 CFU/g in fermented cereal matrices [69].…”
Section: Viability Of Bb-12 R and Lgg R During Storagesupporting
confidence: 93%
“…CFU of BB-12 ® ranged from 1.8 × 10 7 to 3.2 × 10 8 CFU/g (Graph A, Figure 2 ). These values are in line with the results that were obtained by Pavunc et al, who reported BB-12 ® growth to be higher than 10 6 CFU/g in fermented cereal matrices [ 58 ]. There was a significant interaction between the base and the storage time as well as the culture combination.…”
Section: Resultssupporting
confidence: 92%
“…Delivery of the maximal number of viable L. fermentum D12 cells to the colon is decisive to its functionality. Sustaining the viability of probiotic cells during processing and storage is crucial [ 29 , 30 ]. Follow-up experiments included the microencapsulation of L. fermentum D12 bacterial cells in alginate with the addition of different prebiotic substrates, to assess the potential of protecting cells during storage and subsequently the delivery of sufficient viable cells to the colon.…”
Section: Resultsmentioning
confidence: 99%